Retinoic acid (RA) and As(2)O(3) treatment in transgenic models of acute promyelocytic leukemia (APL) unravel the distinct nature of the leukemogenic process induced by the PML-RARα and PLZF-RARα oncoproteins - Rego, Eduardo M. (The National Academy of Sciences, 2000)
Acute promyelocytic leukemia (APL) is associated with chromosomal translocations always involving the RARα gene, which variably fuses to one of several distinct loci, including PML or PLZF (X genes) in t(15;17) or t(11;17), respectively. APL in patients harboring t(15;17) responds well to retinoic acid (RA) treatment and chemotherapy, whereas t(11;17) APL responds poorly to both treatments, thus defining a distinct syndrome. Here, we show that RA, As(2)O(3), and RA + As(2)O(3) prolonged survival in either leukemic PML-RARα transgenic mice or nude mice transplanted with PML-RARα leukemic cells. RA + As(2)O(3) prolonged survival compared with treatment with either drug alone. In contrast, neither in PLZF-RARα transgenic mice nor in nude mice transplanted with PLZF-RARα cells did any of the three regimens induce complete disease remission. Unexpectedly, therapeutic doses of RA and RA + As(2)O(3) can induce, both in vivo and in vitro, the degradation of either PML-RARα or PLZF-RARα proteins, suggesting that the maintenance of the leukemic phenotype depends on the continuous presence of the former, but not the latter. Our findings lead to three major conclusions with relevant therapeutic implications: (i) the X-RARα oncoprotein directly determines response to treatment and plays a distinct role in the maintenance of the malignant phenotype; (ii) As(2)O(3) and/or As(2)O(3) + RA combination may be beneficial for the treatment of t(15;17) APL but not for t(11;17) APL; and (iii) therapeutic strategies aimed solely at degrading the X-RARα oncoprotein may not be effective in t(11;17) APL.